On the profile characteristics of technical surfaces as applied to nanoroughness - V.V. Izmailov; M.V. Novoselova (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
The parameters of the structure of a technical surface at the nanoscale level, determined by the profile method, are considered. The possibility of applying the parameters determined in accordance with domestic and international standards for the roughness profile (microscale level) to the characteristics of the surface at the nanoscale level, which goes beyond the standards, is shown. This possibility is provided by the model of the profile of a technical surface that underlies modern standards as an implementation of a broadband random normal process. An experimental verification of the normality of the process was carried out by comparing the experimental values of the integral probability distribution function of the profile ordinates with theoretical values that obey the normal distribution. The experimentally obtained values of the nine most important parameters, as well as their some relationships between them, are presented, confirming the reliability of the surface profile model as a normal random process. The use of standard surface profile parameters ensures to avoid errors and misunderstandings associated with ambiguous interpretation of one or another parameter.